Short Communication: Novel Single Nucleotide Polymorphisms (SNPs) in the 5'UTR of Bovine Heat Shock Protein 70 (bHSP70) Gene and its association with Service per Conception (S/C) of Pasundan cattle - SYAHRUDDIN SAID; WIDYA PINTAKA BAYU PUTRA (Biodiversitas Journal of Biological Diversity, 2018)
Said S, Putra WPB. 2018. Short Communication: Novel Single Nucleotide Polymorphisms (SNPs) in the 5'UTR of Bovine Heat Shock Protein 70 (bHSP70) Gene and its association with Service per Conception (S/C) of Pasundan cattle. Biodiversitas 19: 1622-1625. Heat stress in the livestock reduces reproductive traits, including of service per conception (S/C). The influence of heat stress in livestock can be handled through molecular selection. One of the candidate genes that is affecting heat stress tolerance is Bovine Heat Shock Protein 70 (bHSP70) gene. This research was carried out to detect the single nucleotide polymorphism (SNPs) in the 5'UTR of bHSP70 gene from 44 heads of Pasundan cows at breeding station (BPPIBT-SP Ciamis, West Java). Research showed that 18 SNPs were detected with sequencing method. The insertion mutation was detected in all animal studied and occurred at position between g.1112 and g.1113. The moderate of polymorphic informative content (PIC) were detected in two SNPs of g.1117G/A and g.1125A/C. Preliminary analysis showed that haplotype of two homozygote genotype combination from both SNPs had better of S/C value of than the others (P<0.01). Moreover, the average of S/C value in heterozygote genotype seems higher than homozygote genotype. However, the further research for clarification of this research results through large number of observation is important. It was concluded that two SNPs of g.1117G/A and g.1125A/C are potential as marker-assisted selection (MAS) for reproductive traits in Pasundan cows because of moderate PIC value.